Hubungan antara Kepatuhan Cuci Tangan terhadap Kasus Diare di Ruang Anak - Tri Wahyuti; Indra Tri Astuti; Nopi Nur Khasanah (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Diarrhea remains a major public health problem among children in Indonesia, with a high prevalence that impacts morbidity, mortality, and child development. One of the key risk factors is non-compliance with hygiene practices, particularly handwashing behavior. This study aimed to determine the relationship between handwashing compliance and diarrhea cases among children treated in the Pediatric Ward of Dahlia, RSUD Dr. H. Soewondo Kendal. The research employed a quantitative analytic method with a cross-sectional design, involving a total sampling of 39 child respondents aged 5–10 years who met the inclusion criteria. Data were collected using a handwashing compliance questionnaire and a diarrhea incidence questionnaire, and analyzed using Spearman’s Rank Correlation test. The results showed that most respondents were in the moderately compliant (53.8%) and compliant (43.6%) categories for handwashing, while the incidence of diarrhea remained relatively high at 51.3%. Bivariate analysis indicated a significant negative relationship between handwashing compliance and diarrhea cases (ρ = -0.538; p = 0.000), meaning that the higher the level of handwashing compliance, the lower the incidence of diarrhea. In conclusion, handwashing compliance is an important protective factor in reducing the risk of diarrhea among children. These findings emphasize the need for continuous education for children and parents regarding proper handwashing practices, as well as the integration of Clean and Healthy Living Behavior (PHBS) promotion into healthcare and educational services to prevent diarrhea from an early age